Efforts To Improve Students' Learning Outcomes Through The Problem Based Learning (PBL) Model With The Tpack Approach On The Material Of Intelligent - Manurung, Siti Aminah; Lase, Umbuzaro (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2021)
This research started from the problem of the low mathematics learning outcomes, Regency on the Integerate Number material, under the Minimum Completeness Criteria (KKM) which is 67. Of the 21 total students, only 9 students reached the KKM, which is approx. 44%. The purpose of this study was to improve the learning outcomes of eighth grade students of SMP Negeri 2 Mandrehe. This research is a classroom action research (CAR) which is carried out in two cycles. This research was conducted in class VII of SMP Negeri 3 One Roof Idanotae in the 2018/2019 academic year. Based on the results of the discussion and analysis, it is concluded that the application of problem based learning (PBL) learning models can improve student learning outcomes in the Numbers material. The increase in teacher activity in the learning process is caused by the teacher using a problem based learning (PBL) learning model. Student learning outcomes have increased from cycle I to cycle II. Student learning outcomes before the action that reached the KKM were only 9 students with a classical average of 44%. Then in the first cycle, only 15 students reached the KKM with a classical average of 67%. Cycle II students who reach the KKM 19 students with a classical average of 93%.